Evaluation of microbiological purity of nasal ointment "Mnemastym" - Al Nukari Abdulkarim; О. S. Koshelev; A. L. Drozdov (Zaporozhye State Medical University, 2018)
The aim of this work was the determination of microbiological purity of nasal ointment "Mnemastym" with arginine-vasopressin (AVP). Materials and methods. For the microbial contamination control the inoculations were made on the nutrient medium set: for colibacillus - Endo agar, for staphylococcus - vitelline-saline agar and for fungi - Sabouraud's glucose agar. Petri dishes with inoculations were incubated during 48 hours at the tempereture 37 °C. Next identification was carried out by the traditional method. Results. It was determined that amount of microorganisms (bacteria and fungi) in 1 g of composition isn't more than allowable standard by State Pharmacopoea of Ukraine for this class of dosage forms, but lies near critical value. It is sufficient for extemporaneous compounding of nasal ointment "Mnemastym" but at the same time development of further manufacturing of drug with the adding of antiseptic excipients is necessary. On the base of complex pharmaco-technological, biopharmaceutical, physical-chemical, rheological and biological investigations the optimal composition and technology for compounding of nasal ointment "Mnemastym" for the therapy of cognitive consequences of cerebrovascular pathology were developed. Conclusions. It was determined that manufacturing of nasal dosage form "Mnemastym" needs an adding of excipients with antimicrobial activity for stabilization of microbial contamination process. It was revealed that for the minimization of this standardization value for the ointment on lipophilic base in pharmacopoeia limit using of polyhexamethylenguanidin phosphate of triclozane or mixture of nipagin: nipazole 8:2 in 0.15 % concentration is the most rationale. Adding of preservatives in nasal ointment with vasopressin on lipophilic base for extemporaneous compounding isn't need.